The Context and Contextual Constructs of Research - Knight, Shirlee-Ann; Halkett, Georgia; Cross, D. (Queensland University of Technology Publications, 2010)
This paper presents the Contextual Constructs Model (CCM) and the theory which underpins it, Contextual Constructs Theory (CCT). Developed as part of a complex project designed to investigate user perceptions of Information Quality (IQ) in the context of Web-based Information Retrieval (IR), the CCM is not a single research method per se. Instead, CCT/CCM is a modelled research framework providing an over-arching approach to scientific investigation, by which a researcher is able to identify multiple possible methods of study and analysis according to the identified research constructs and their contexts. Central to CCT is that all research involves the fusion of two key component parts; that of (1) context; and (2) cognitively-driven constructs; and that the co-dependent nature of the relationship between these components inform the research process, development and eventual outcomes. The resulting CCM framework is one which scaffolds research as a contextual process of phases, identifying the conceptual; philosophical, implementation, and evaluation tasks associated with a complex research investigation. The underlying epistemology of such a contextual approach to research is said to be a blend of a critical-real world view within a systems-science approach to investigation.